Assessment of sexualuty in male patients with diabetes mellitus - Masilionis, Giedrius; Palinauskienė, Liucija Ramunė (Slauga. Mokslas ir praktika, 2020)
While in Lithuania there are growing people in diabetes amount, there are also growing complications caused by diabetes. One of these complications is sexual dysfunction. There are not many research in Lithuania related to this problem. For people in diabetes cardiovascular system is damaged very soon. A penis blood vessel, which delivers blood to it, is very narrow and that is why people in diabetes firstly feel sexual dysfunction symptoms. In 1970 World Health Organization pointed sexual health like one of the most important in human life quality. Erectile disorders are typical from 35 to 90 percent of people in diabetes. For these people, erectile disorders start 10 – 15 years earlier than healthy men. The aim – to evaluate men in diabetes sexuality. Research methods – questionnaire according to the EMAS SFQ, which is valid and used in European Male Aging Study. Translated questionnaire already was used in a research of healthy and type 1 diabetes men sexual function. Respondent have to be sexual active in a period of 4 weeks. Questions involve 4 main sexuality domains: overall sexual function, sexual distress, changes of sexual function in one year and masturbation. Research was performed from the 3 rd of September 2018 to the 1 st of October 2018 by uploading the questionnaire to the Facebook platform closed group „x“ and in association of diabetes. There were examined 42 men in type 1 or type 2 diabetes, from 26 to 69 years old. Conclusions: men in diabetes have erectile dysfunction three times more often than healthy men. erectile disorders are typical from 35 to 90 percent of people in diabetes. According to the evaluated men‘s sexuality domains it is clear that masturbating index was declined and sexual function distress was inclined. Overall sexual function and changes of sexual function in one year changed ot much. For the majority of respondents, their sexual life in one year changed faintly.